MiR-101 attenuates myocardial infarction-induced injury by targeting DDIT4 to regulate autophagy - Li, Qiulan; Gao, Yanping; Zhu, Jie; Jia, Qingzhe (Current neurovascular research, 2020)
Myocardial infarction (MI)，a kind of heart deficiency is a main cause of death and disability. Autophagy, a metabolic process for degradation of damaged proteins or organelles, is important for cardiac functions and regulated by several miRNAs including miRNA-101. This research was aim to investigate the effects of miR-101 in myocardial infarction-induced injury and the related mechanisms. MI model was induced by ligation of the left coronary artery. The in vitro model was established by hypoxia induced H9c2 cells (rat myocardial cells). The overexpression of miR-101 was achieved by transfection. The expression of associated proteins was analyzed by Western blotting. The level of miR-101 was analyzed by reverse transcription-polymerase chain reaction (RT-PCR). The target genes for miR-101 and the target sites were analyzed by TargetScan. The results showed that miR-101 was decreased in MI mice (p<0.01). Autophagy and apoptosis were increased in MI-induced injury (in vivo) and in hypoxia treated myocardial cells (in vitro) (p<0.01). miR-101 overexpression inhibited the increasing of autophagy and apoptosis in mice and in myocardial cells (p<0.01). DDIT4 was a target gene of miR-101 and expressed increasingly in MI-induced injury mice and hypoxia treated myocardial cells. miR-101 could negatively regulated the expression of DDIT4. This research suggested that miR-101 attenuatedMI-induced injury by targeting DDIT4 to regulate autophagy, which indicated that miR-101 or DDIT4 may be potential therapeutic targets for heart injury.